The movement and migration of shrimp, Penaeus semisulcatus in Bushehr Coastal Waters, Persian Gulf - Niamaimandi, Nassir; Arshad, Aziz; Daud, Siti Khalijah; Saed, Che Roos; Kiabi, Bahram (Asian Fisheries Society, 2010)
The pattern of movement of green tiger prawn, Penaeus semisulcatus, was carried out in Bushehr waters, Persian Gulf, in 2003 and 2004. During this experiment 2571 shrimps, P. semisulcatus were tagged with green polyethylene steamer tags and released at sea from January 2003 to July 2004. During the open season of shrimps (August and September), 68 shrimps were recaptured but four of the recaptures were excluded due to inconstancies of information. The direction of movement of recaptures was mostly to the north west of the release area and to deeper waters. The majority of recaptures exhibited speed of less than 2 km/day and maximum speed was recorded at 3-4 km/day. The longest distance of 127 km was performed by a female during 95 days liberty. In the Persian Gulf the main of sea current is from the Strait of Hormuz to the Iranian waters, and probably influences the pattern of shrimp movement in the Bushehr area.